Pengaruh Model Picture And Picture terhadap Hasil Belajar Siswa pada Subtema 2 Hidup Rukun dengan Teman Bermain pada Kelas II SD Negeri 091316 Pematang Raya - Yesi Tri Cayani Sinaga; Lisbet N. Sihombing; Eva Pasaribu (Multiverse: Open Multidisciplinary Journal, 2022)
The purpose from research is to know the effect model picture and picture to study result students at subtema 2 hidup rukun dengan teman bermain to class II SD Negeri 091316 pematang raya.this research is a experiment with design quasi experiment.design used in research is pretest and posttest sample fro. Research in class experiment is class II-A class in SD negeri 091316 pematang raya and research sample in control class is students II-B class in SD negeri 091316 pematang raya.based analysis result and from explain from research data by test result hypothesis with t-test where t-table : 3,69 if score significant (2- tailed) < 0,05 ,so can different significant from result study students to experiment class and control class.the result from this research the score significant (2-tailed) : 0,001.so Ho not significant and ha significant.based the results from the effect model picture and picture to result study students in sub tema 2 hidup rukun dengan teman bermain in class II SD negeri 091316 Pematang Raya